Cleft palate surgical perspectives: A pilot study - Danielle DeWitt; Christina Nobriga (Wolters Kluwer Medknow Publications, 2023)
Purpose: The current pilot study aimed to collect craniofacial surgeon's personal perspectives regarding the timing of cleft palate surgical repair, medical considerations for surgical repair (i.e., age, weight, type of cleft, and potential for surgical complications), and social considerations (i.e., speech-language development, socioeconomic status, and familial support). Materials and Methods: Fifteen plastic surgeons currently practicing cleft palate repair participated in this study. Surveys were distributed electronically to team coordinators of the American Cleft Palate-Craniofacial Association-accredited craniofacial teams and included a combination of Likert scales, closed multiple-choice questions, and open-ended qualitative questions for free-text responses. Results: Preliminary data obtained in this study suggest that the most common age range for palate repair in nonmedically complex infants is 10-11 months of age (n = 10). Notably, 20% of respondents (n = 3) reported a typical surgical repair time of 7-9 months of age. While medical and social priorities differed, all surgeons rated speech-language development as an important factor when determining the timing of surgical intervention. Conclusion: Given the limited consensus on surgical timing and intervention for children with cleft palate, further research is needed to determine the optimal timing of palate repair that considers both medical safety and near age-appropriate speech sound acquisition and production.